Management and feeding aspects of the Pelibuey sheep breeder in Cuba - Herrera, Javier; Jord?n, Humberto; Senra, Andr?s Francisco (Cuban Journal of Agricultural Science, 2010)
The purpose of this review is to highlight the principal traits of the Pelibuey sheep breeder, some elements of management, feeding and its situation in Cuba. Most of the management and feeding systems for the rearing of these animals are classified as extensive. The climatic conditions and the feed availability are the factors affecting the most the reproductive performance of sheep in the tropics. The cycle of sheep production has three important stages: pregnancy, lactation, and dry period. Probably, the energy deficiency is the one affecting the most the performance of these animals, as compared with any other nutritive deficiency. The grazing sheep breeders are exposed to different biotic and abiotic factors provoking physiological and metabolic unbalances that influence directly the productive efficiency. The pathologies are one of these factors. The feeding system exerts marked influence on the productive yield of the Pelibuey breeder, in all the indicators related to it. Key words: Pelibuey breeder, management, feeding.